Principles of Accounting Calculations in Sharia Banking - Suci Mardiyah; Syafnur Muhammad Rizky; Mifta Hasda; Hidayat Hidayat; Wahyu Febri Ramadhan Sudirman; Rinda Fithriyana (Global Sustainability Research Institute, 2024)
Introduction: This article aims to provide a better understanding of Accounting Principles in Islamic Banking. Methods: The research method used is the literature research method or literature review. The purpose of literature research is to understand existing understanding of a research topic, identify knowledge gaps, and provide a conceptual basis for further research. Results: The research results provide a better understanding of the calculations and accounting treatment of sharia banking products, as well as discussing the importance of compliance with Islamic sharia principles in sharia banking operations. Conclusion and suggestion: This article highlights the importance of research and a deeper understanding of calculations and accounting treatment in sharia banking products to strengthen accounting practices following sharia principles. The implication of this article is to increase understanding and awareness of sharia banking among the wider community. With a better understanding of how Islamic banking operates and how their financial products and services are managed accounting, people can make smarter financial decisions that comply with sharia principles.